Cross-Cultural Pragmatics Analysis in the Speech of European and Indonesian Football Match Commentators - Fadillah, Arif (DBSMB, Vocational College of Universitas Gadjah Mada, 2023)
This study aims to describe the form of pragmatic speech acts and the form of comparison in football match commentators in Europe and Indonesia. This research will focus on contrasting the speech forms of football match commentators in Europe and commentators in Indonesia. The data in this study are in the form of speech of football match commentators in Europe and in Indonesia. The data were obtained from YouTube accounts of football matches. After the data is found and recorded, the researcher conducts data reduction. After the data is reduced, the researcher analyzes the data. This research uses speech act theory to describe each comment. After the types of speech acts in the two languages are described, the researcher then constructs each form of comment in both languages. This study found that illocutionary speech acts are found in football commentators in Europe and Indonesia. However, the illocutionary speech act of expression of gratitude is only found in Indonesian football commentators. In addition, the forms of utterances in football commentary are influenced by social factors such as religion and history. This research will contribute to seeing the distinctive forms of speech of football commentators in Europe and Indonesia.